2014
DOI: 10.1080/09583157.2014.982511
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic colonisation of tobacco, corn, wheat and soybeans by the fungal entomopathogenBeauveria bassiana(Ascomycota, Hypocreales)

Abstract: We demonstrate the effectiveness of three inoculation methods (foliar spray, seed immersion and root immersion) in establishing fungal the entomopathogen Beauveria bassiana as an endophyte in tobacco, corn, wheat and soybean. Colonisation of leaves by B. bassiana was assessed 7, 14, 21 and 28 days postinoculation. There were significant differences (p < 0.001) in endophytic colonisation among the different inoculation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 24 publications
4
68
0
12
Order By: Relevance
“…Selection of this fungal strain was based on its laboratory efficacy against other common pest insects in Argentina (Pelizza et al 2012a, b). The species was identified using both molecular (GenBank accession number KF500409) and morphological data, as described by Russo et al (2015).…”
Section: Fungal Isolatementioning
confidence: 99%
See 1 more Smart Citation
“…Selection of this fungal strain was based on its laboratory efficacy against other common pest insects in Argentina (Pelizza et al 2012a, b). The species was identified using both molecular (GenBank accession number KF500409) and morphological data, as described by Russo et al (2015).…”
Section: Fungal Isolatementioning
confidence: 99%
“…Beauveria bassiana is an entomopathogenic fungus with worldwide distribution, which can live as a plant endophyte and usually does not cause visible damage to the host (Van Bael et al 2005). It has been naturally isolated from several plant species, and artificially introduced into many others, such as tomato (Solanum lycopersicum L.) (Ownley et al 2004), banana (Musa paradisiaca L.) (Akello et al 2007), coffee (Coffea arabica L.) (Posada et al 2007), sorghum (Sorghum bicolor Kuntze) (Reddy et al 2009), pine (Pinus radiata D. Don) (Brownbridge et al 2012), tobacco (Nicotiana tabacum L.), corn (Zea mays L.), wheat (Triticum aestivum L.) and soybeans (Glycine max L.) (Russo et al 2015) by using various techniques. Colonization of plant tissues by B. bassiana has proved to provide protection against insect damage and inhibition of insect establishment and development (Ownley et al 2004;Vega et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the naturally occurring Beauveria strain may have already been present in the field. An endophytic relationship between B. bassiana and soybean following seed inoculation was reported by Russo et al (2015); however, the endophyte diminished over time. Here, the extended time between planting and sampling during bloom would have likely mitigated any beneficial effects of Beauveria seed treatments.…”
Section: Managing Kudzu Bug With Foliar-and Seed-applied Beauveria Bamentioning
confidence: 94%
“…Conidia persist in the soil and can be dispersed by wind, rain splash, or infected hosts (Inglis et al, 2001; Ulevičius et al, 2004; Meyling and Eilenberg, 2007). Endophytic relationships between B. bassiana and several crop plants, including soybean, are reported (Russo et al, 2015; Vidal and Jaber, 2015).…”
mentioning
confidence: 99%
“…In the endophytic state, there is potential to exploit the fungus for induced systemic resistance to biotic and/or abiotic stressors (Rodriguez et al, 2009). Moreover, as a host plant, T. aestivum appears endophytic-friendly, both as natural host (Crous et al, 1995;Larran et al, 2002Larran et al, , 2007Vujanovic et al, 2012;Comby et al, 2016;Grudzinska-Sterno et al, 2016) and when artificially inoculated (Dingle and McGee, 2003;Gurulingappa et al, 2010;Russo et al, 2015;Sánchez-Rodríguez et al, 2015;Sánchez-Rodríguez et al, 2018). In a recent review on EPF as endophytes in biological control, Vega (2018) found that 40% (34/85) of papers covered examined plant responses to endophytism, covering 20 plant species.…”
Section: Introductionmentioning
confidence: 99%